2022
DOI: 10.1096/fj.202101469rr
|View full text |Cite
|
Sign up to set email alerts
|

β‐Hydroxybutyric acid attenuates heat stress‐induced neuroinflammation via inhibiting TLR4/p38 MAPK and NF‐κB pathways in the hippocampus

Abstract: Heat stress causes many pathophysiological responses in the brain, including neuroinflammation and cognitive deficits. β‐Hydroxybutyric acid (BHBA) has been shown to have neuroprotective effects against inflammation induced by lipopolysaccharide. The aim of the present study was to evaluate the effects of BHBA on neuroinflammation induced by heat stress, as well as the underlying mechanisms. Mice were pretreated with vehicle, BHBA or minocycline (positive control group) and followed by heat exposure (43°C) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…In the current study, overproduced TLR4 was found in the hippocampus of HS broilers regardless of dietary treatments ( P < 0.05, Figure 2A and B ). Similarly, overregulation of TRL4 in the hippocampus has been found in heat stress-induced neuroinflammation in mice ( Huang et al, 2022 ).
Figure 2 The effects of temperature and Bacillus subtilis -based probiotic on hippocampal (A) TLR4 protein concentrations, (B) TLR4 mRNA expressions, (C) HSP70 protein concentrations, and (D) HSP70 mRNA expressions in broilers at 43 d of age.
…”
Section: Resultsmentioning
confidence: 78%
“…In the current study, overproduced TLR4 was found in the hippocampus of HS broilers regardless of dietary treatments ( P < 0.05, Figure 2A and B ). Similarly, overregulation of TRL4 in the hippocampus has been found in heat stress-induced neuroinflammation in mice ( Huang et al, 2022 ).
Figure 2 The effects of temperature and Bacillus subtilis -based probiotic on hippocampal (A) TLR4 protein concentrations, (B) TLR4 mRNA expressions, (C) HSP70 protein concentrations, and (D) HSP70 mRNA expressions in broilers at 43 d of age.
…”
Section: Resultsmentioning
confidence: 78%
“…Upon binding, GPR109a activates anti‐inflammatory signaling pathways, including Nrf2/HO‐1, and reduces p38 MAPK and NF‐κB signaling (Viatchenko‐Karpinski et al, 2022; Zhang et al, 2022). This is supported by in vivo data, demonstrating a reduction in microglial p38 MAPK/NF‐κB signaling following BHB supplementation in a heat‐stress model of neuroinflammation (Huang et al, 2022). The ketogenic diet is used clinically as non‐pharmacological adjuvant therapy for neurological disorders, such as multiple drug‐resistant epileptic syndromes where it significantly reduces the number and frequency of epileptic seizures (Caraballo, Flesler, et al, 2014; Caraballo, Fortini, et al, 2014; Sondhi et al, 2020; Wang et al, 2020).…”
Section: Ketone Bodies Inhibit Microglial Activationmentioning
confidence: 68%
“…Although several reports have described biochemical and neurophysiological changes occurring in the hippocampus following heat stress (Lee et al 2015 ; Moon et al 2017 ; Elvira et al 2020 ; Huang et al 2022 ), the impact of heat stress on adult hippocampal neurogenesis has been largely unaddressed. BHBA, a ketone body, has been shown to have neuroprotective roles in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that BHBA processed properties of excellent anti-inflammatory effects in heat stress-treated mice (Huang et al 2022 ). Besides, the effects of heat stress on adult hippocampal neurogenesis and the underlying connections to cognitive dysfunction are unclear.…”
Section: Introductionmentioning
confidence: 99%